2021
DOI: 10.1021/acs.joc.1c01513
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Diverse Spiro-oxindole-fluorene Derivatives via a DABCO-Promoted Annulation Reaction of Bindone and 3-Methyleneoxindoles

Abstract: A DABCO-promoted annulation reaction of bindone ([1,2′-biindenylidene]-1′,3,3′-trione) and 3-methyleneoxindoles showed very interesting molecular diversity under different reaction conditions. The base-promoted annulation reaction of bindone and 3-phenacylideneoxindoles in DCM at room temperature afforded spiro[indeno[1,2-a]fluorene-5,3′-indoline] derivatives in good yields and with high diastereoselectivity. However, the similar reaction of 2-(2-oxoindolin-3-ylidene) acetates resulted in Z/E-isomeric spiro[in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 92 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…For explaining the mechanism of the above formal [3 + 3] and [4 + 2] cycloaddition reactions, a plausible reaction mechanism was proposed as shown in Scheme 2 according to the known results 11 and present experiments. Firstly, a carbanion ( A ) was formed by deprotonation of bindone in the presence of a base.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For explaining the mechanism of the above formal [3 + 3] and [4 + 2] cycloaddition reactions, a plausible reaction mechanism was proposed as shown in Scheme 2 according to the known results 11 and present experiments. Firstly, a carbanion ( A ) was formed by deprotonation of bindone in the presence of a base.…”
Section: Resultsmentioning
confidence: 95%
“…9,10 In recent years, we successfully found that bindone can be easily in situ generated by base catalyzed dimerization and sequentially undergoes an interesting annulation reaction to give diverse indanone-containing polycyclic compounds. 11 In this respect, it has been found that the triethylamine promoted reaction of 1,3-indanedione with 3-arylideneindolin-2-ones in ethanol gave the carbamato-substituted indeno[1,2- a ]fluorenes, in which the reactive bindone was in situ generated to undergo a formal [4 + 2] addition reaction and a further ring-opening process (eqn (1) in Scheme 1). 11 a The base promoted annulation reaction of bindone with 3-phenacylideneoxindoles in DCM at room temperature afforded novel spiro[indeno[1,2- a ]fluorene-5,3′-indoline] derivatives through formal [4 + 2] cycloaddition reaction processes (eqn (2) in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…By using 2-arylidene-1,3-indanediones as key substrates, we have developed a couple of domino multicomponent reactions for providing easy access to diverse novel indanone-containing polycyclic systems. 11–13 Recently, we successfully found that the three-component reaction of alkyl glycinate hydrochloride, dialkyl but-2-ynedioate and 2-arylidene-1,3-indanediones in ethanol resulted in functionalized dihydrospiro[indene-2,3′-pyrrolidines]. 14 In this reaction a new type of azomethine ylide was generated from the reaction of alkyl glycinate and dialkyl but-2-ynedioate, which in turn underwent [3+2] cycloaddition reaction with 2-arylidene-1,3-indanedione.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Yan and coworkers have reported a selective synthesis of spiro[benzo[5,6]pentaleno[1,6 a - b ]naphthalene-7,3 ' -indoline] derivatives and complex dispiro[indoline-3,6 ' -[4 b ,6 a ]-ethanoindeno[1,2- a ]fluorene-14 ' ,3 '' -indolines] via a DABCO-promoted annulation reaction of bindone and 3-methyleneoxindoles in acetonitrile at various temperatures for the in optimized yields (Fig. 4 ) 23 .
Figure 2 Condensation of 1,3-indanedione in basic or acidic conditions.
…”
Section: Introductionmentioning
confidence: 99%